2007
DOI: 10.1007/s11104-007-9381-7
|View full text |Cite
|
Sign up to set email alerts
|

The change of soil carbon stocks and fine root dynamics after land use change from a native pasture to a pine plantation

Abstract: A published meta-analysis of worldwide data showed soil carbon decreasing following land use change from pasture to conifer plantation. A paired site (a native pasture with Themeda triandra dominant, and an adjacent Pinus radiata plantation planted onto the pasture 16 years ago) was set up as a case study to assess the soil carbon reduction and the possible reason for the reduction under pine, including the change in fine root (diameter <2 mm) dynamics (production and mortality). Soil analysis confirmed that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 41 publications
5
57
0
3
Order By: Relevance
“…The only soil property correlated with R. ferrugineum cover was C content. Other studies also reported higher contents of organic C in forest than in grasslands (Guo et al 2007;Guidi et al 2014). As a consequence of reduced soil temperature and moisture following forest succession (Hiltbrunner et al 2013), the decomposition of organic matter is slowed down, leading to a decreased incorporation of C into soil aggregates (Gregorich et al 2006).…”
Section: Cover Of R Ferrugineum Is Related To the Distribution Of Fimentioning
confidence: 95%
“…The only soil property correlated with R. ferrugineum cover was C content. Other studies also reported higher contents of organic C in forest than in grasslands (Guo et al 2007;Guidi et al 2014). As a consequence of reduced soil temperature and moisture following forest succession (Hiltbrunner et al 2013), the decomposition of organic matter is slowed down, leading to a decreased incorporation of C into soil aggregates (Gregorich et al 2006).…”
Section: Cover Of R Ferrugineum Is Related To the Distribution Of Fimentioning
confidence: 95%
“…Soil C stocks generally increase on depleted ex-croplands, and remain unchanged or decrease on ex-grasslands and ex-pastures with the progressive disappearance of their abundant root litter [42][43][44][45][46]. For example, Guo et al [47] observed, in an afforested pasture with pines, that the loss of soil C was positively correlated with the mortality volume of fine roots. However, fine root dynamic (production and mortality) was not measured in our study.…”
Section: Soilmentioning
confidence: 99%
“…Isto altera atributos químicos, físicos e biológicos e esta alteração pode ser intensificada com práticas de manejo do solo (Guo et al, 2007). Assim, o estudo dessas superfícies torna-se premissa básica nos levantamentos pedológicos, na tomada de decisões em relação ao manejo do solo, intensidade e frequência de amostragem e gerenciamento de práticas agrícolas e avaliação dos efeitos da agricultura sobre a qualidade ambiental (Corá et al, 2004).…”
Section: Introductionunclassified